STRATEGI MARKETING PEMBIAYAAN BANK SYARIAH DALAM MENDUKUNG PENGEMBANGAN UMKM DI INDONESIA - Anita Sari, Cindy; Intan Azzahra; M. Royhan Safdan Muzaki (Academic Solution Publisher, 2025)
This study is motivated by the strategic role of Islamic banks in strengthening the financing of Micro, Small, and Medium Enterprises (MSMEs), which are key drivers of Indonesia’s economic growth. The purpose of this research is to analyze the marketing strategies of Islamic bank financing in supporting MSME development. A qualitative research approach was employed using SWOT analysis as the primary method to examine the strengths, weaknesses, opportunities, and threats influencing the effectiveness of Sharia financing marketing. The findings reveal that Sharia-compliant values, flexible financing contracts, strong community networks, and personalized services constitute major strengths of Islamic banks, while low literacy on Sharia contracts, limited digitalization, uneven staff competencies, and restricted branch coverage represent internal weaknesses. Externally, MSME growth, increasing demand for halal financial products, and supportive government policies provide opportunities, whereas competition from conventional banks, fintech platforms, online lending, and low financial literacy pose significant threats. The study concludes that marketing strategies must reinforce Sharia-based approaches and accelerate digital transformation. Recommendations include enhancing Sharia literacy, promoting financing product innovation, and strengthening communitybased marketing.